Chemistry pumps: a review of chemically powered micropumps. Issue 10 (22nd April 2016) - Zhou, Chao; Zhang, Hua; Li, Zeheng; Wang, Wei
Abstract : Lab-on-a-chip devices have over the recent years attracted a significant amount of attention in both academic circles and industry, due to their promise in delivering versatile functionalities with high throughput and low sample amount. Abstract : Lab-on-a-chip devices have over recent years attracted a significant amount of attention in both the academic circle and industry, due to their promise in delivering versatile functionalities with high throughput and low sample amount. Typically, mechanical or electrokinetic micropumps are used in the majority of lab-on-a-chip devices that require powered fluid flow, but the technical challenges and the requirement of external power associated with these pumping devices hinder further development and miniaturization of lab-on-a-chip devices. Self-powered micropumps, especially those powered by chemical reactions, have been recently designed and can potentially address some of these issues. In this review article, we provide a detailed introduction to four types of chemically powered micropumps, with particular focus on their respective structures, operating mechanisms and practical usefulness as well as limitations. We then discuss the various functionalities and controllability demonstrated by these micropumps, ending with a brief discussion of how they can be improved in the future. Due to the absence of external power sources, versatile activation methods and sensitivity to environmental cues, chemically powered micropumps could find potential applications in a wide range of lab-on-a-chip devices.